2021
DOI: 10.3390/cancers13123102
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Lymphoblastic Lymphoma Arising in the Setting of Myeloid/Lymphoid Neoplasms with Eosinophilia: LMO2 Immunohistochemistry as a Potentially Useful Diagnostic Marker

Abstract: Background: Rarely, T-lymphoblastic lymphoma (T-LBL) may develop in the setting of myeloid/lymphoid neoplasms with eosinophilia (M/LNs-Eo), a group of diseases with gene fusion resulting in overexpression of an aberrant tyrosine kinase or cytokine receptor. The correct identification of this category has relevant therapeutic implications. LIM domain only 2 (LMO2) is overexpressed in most T-LBL, but not in immature TdT-positive T-cells in the thymus and in indolent T-lymphoblastic proliferations (iT-LBP). Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…T‐LBL is a rare and aggressive form of precursor T‐cell non‐Hodgkin's Lymphomas (T‐NHLs) affecting mainly children and young adults and involving lymph nodes, BM and thymus. 1 T‐LBL represents around 85% of all immature lymphoblastic lymphomas, whereas immature B‐cell.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T‐LBL is a rare and aggressive form of precursor T‐cell non‐Hodgkin's Lymphomas (T‐NHLs) affecting mainly children and young adults and involving lymph nodes, BM and thymus. 1 T‐LBL represents around 85% of all immature lymphoblastic lymphomas, whereas immature B‐cell.…”
Section: Discussionmentioning
confidence: 99%
“…T‐lymphoblastic lymphoma (T‐LBL) is an aggressive malignancy of T‐lymphoid precursors, which can rarely co‐occur with Myeloid/Lymphoid Neoplasms with Eosinophilia (M/LNs‐Eo). 1 Acquired genetic and epigenetic aberrations affect the early thymocyte subset leading to the formation of T‐LBL and T‐ALL malignancies. T‐ALL and T‐LBL are commonly found amongst children and young adults, manifesting in 15% of the ALL cases, whereas T‐LBL affects 20% of the non‐Hodgkin lymphomas (NHLs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMO2 is highly expressed in the majority of T-LBLs, whereas it is not observed in undeveloped TdT-positive T cells in the thymus or slow-growing T-lymphoblastic growths. Out of 11 cases of T-LBLs linked to myeloid/lymphoid neoplasms with eosinophilia, a study found that nine of them did not have LMO2, indicating a distinct molecular process for T-LBLs associated with myeloid/lymphoid neoplasms with eosinophilia [ 25 ]. Interestingly, LMO2 expression is observed in lymphomas derived from germinal center lymphocytes, including FL, Burkitt lymphoma (BL), and DLBCL, as well as in NLPHL [ 18 ].…”
Section: Reviewmentioning
confidence: 99%
“…At present, T-cell lymphoblastic lymphoma and T-cell acute lymphocytic leukemia (T-ALL) are defined as the same type of disease in clinical practice [4,5]. T-cell lymphoblastic lymphoma is a rare and highly aggressive Hodgkin's lymphoma in clinical practice, which is common in children and adolescents, especially in male children and adolescents [6,7]. At present, the treatment for T-cell lymphoblastic lymphoma in clinical practice is mainly high-dose chemotherapy (HDC) combined with a variety of drugs [8][9][10].…”
Section: Introductionmentioning
confidence: 99%